An edge-based stochastic facility location problem in UAV-supported humanitarian relief logistics: a case study of Tehran earthquake - Golabi, Mahmoud; Shavarani, Seyed Mahdi; Izbirak, Gokhan (Springer, 2017)
The application of facility location problems in choosing the best location of relief distribution centers plays a salient role in emergency operations of large-scale disasters. On the premise that the service recipients are uniformly distributed along the network edges, this study investigates a combined mobile and immobile pre-earthquake facility location problem. A predefined number of locations are to be selected among a set of potential locations. Each facility is used in the relief distribution operation. It is incontrovertible that due to earthquakes, some network edges collapse and corresponding areas may lose their accessibility. Thus in this study, it is assumed that people on intact and accessible edges travel to the location of the distribution centers to receive the relief. For those who are located on collapsed or inaccessible network edges, the medium-scale unmanned aerial vehicle (UAV) helicopters are utilized in the relief distribution operation. This study aims to develop a mathematical model which minimizes the aggregate traveling time for both people and UAVs over a set of feasible scenarios. Since the network problems are NP-hard, some metaheuristic algorithms are developed to solve the proposed model. In order to demonstrate the applicability of developed model, a case study based on feasible earthquake scenarios in Tehran is presented.
Keywords: Facility location; Distributed demand; Metaheuristics; Humanitarian logistics; UAV